Students’ Need to Increase Ethically Acceptable Paraphrasing of Academic Texts - Andi Dian Rahmawan; Yanuar Bagas Arwansyah (English Language Education Department, Universitas Kristen Duta Wacana (UKDW), Yogyakarta, Indonesia, 2023)
The lack of Indonesian students performing their abilities in L1 paraphrasing becomes the primary reason they are labeled as persistent plagiarizers. Students, in Indonesian context and circumstances, need to broaden their perspectives regarding how to document the sources, using them in their original papers to support and defend the arguments. Literacy should be developed sustainably in order for students might critically think and state things with evidence. However, to say that students still developing English writing text as intentional plagiarism will appear to be overly harsh. Teachers, at the university level, should acknowledge that students’ commitment to plagiarism is the process of knowing its definition, characters, impacts, and habit of copying others’ work without any attempt to document it properly. Moreover, it also signs the teachers that students’ ability to use academic English needs improving. Observing these facts urges us to facilitate students to make them ready to conduct the paraphrase of the L2 texts while their EAP is still developing. This study seeks the fundamental preparation that should be made to generate acceptable paraphrasing texts.